Application of XBRL in Financial Reporting: Effects On Preparers and Users of Financial Statements - Boyanov, Borislav (Research Papers, 2024)
This article discusses XBRL as one of the fundamental tools for digitizing the process of accounting, compiling and publishing financial statements. A systematized review of the historical development, technological features of XBRL and its institutional identity are made. It is emphasized that the XBRL standard is widely applied internationally, generally on a voluntary basis, with the exception of a certain range of EU entities that are obliged to prepare and publish their financial statements through the XBRL-based European Single Electronic Format (ESEF). A literature review of the benefits and disadvantages of applying XBRL in the field of accounting and financial reporting is made. The advantages and weaknesses of XBRL from the point of view of accountants and from the point of view of users of financial statements are studied in order to identify the causes of difficulties in the exchange of financial information and to outline proposals for overcoming them.
Keywords: Financial reporting; XBRL; Benefits and disadvantages